The effects of different thickness on microstructure and acoustic properties of oil palm empty fruit bunch natural fibre with density of 160 kg/m3 - Aravindhran A/L Muttalagan (2023)
This research project aims to provide a rational discussion regarding how the thickness variation on morphologies of Low Density Fibreboard (LDF) of Oil Palm Empty Fruit Bunch (OPEFB) affects its respective acoustic properties. Two types of tests were conducted in this project which Sound Absorption Coefficient (SAC) and Scanning Electron Microscope (SEM) test. SAC test were conducted to investigate the acoustic properties of OPEFB while SEM test were conducted to study the morphologies and microstructure.